2016
DOI: 10.1088/0953-2048/30/1/015009
|View full text |Cite
|
Sign up to set email alerts
|

Change of surface critical current in the surface superconductivity and mixed states of superconducting niobium

Abstract: A systematic study of irreversible magnetization was performed in bulk Niobium after different surface treatments. Starting with smooth surfaces and abrading them, a strong increase of the critical current is observed up an apparent limiting value. An impressive change of the critical current is also observed in the surface superconductivity (SSC) state, reaching values of the same order of magnitude as in the mixed state. We explain also the observation of strong SSC for magnetic field perpendicular to larges… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Nevertheless, this value is not always easy to derive from magnetization curves, due to the appearance of a tail at high magnetic fields in some conditions, as in this case [ 41 ]. With this aim, heat capacity, which is essentially a bulk property, could better allow the determination of μ 0 H c2 , as marked by the arrow in Figure 6 b [ 12 , 13 ]. It must be noted that the C ( H ) curve for the FS_N sample (not shown here for clarity reasons) is very similar to that of the reference sample, indicative of similar bulk properties (and μ 0 H c2 ) between both samples.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, this value is not always easy to derive from magnetization curves, due to the appearance of a tail at high magnetic fields in some conditions, as in this case [ 41 ]. With this aim, heat capacity, which is essentially a bulk property, could better allow the determination of μ 0 H c2 , as marked by the arrow in Figure 6 b [ 12 , 13 ]. It must be noted that the C ( H ) curve for the FS_N sample (not shown here for clarity reasons) is very similar to that of the reference sample, indicative of similar bulk properties (and μ 0 H c2 ) between both samples.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the Δ M (or i c ) at fields above H c2 for different surface treatments have been reported by several groups. For example, Scola et al [ 13 ] observed an increase of i c values after irradiating the Nb surface with low-energy Ar + ions; Aburas et al [ 12 ] observed changes by polishing the surface using different processes (sandpaper, diamond, colloidal silica and chemical polishing), with lower i c values for smoother surfaces; Casalbuoni et al [ 10 ] also reported differences in i c values of Nb cylinders subjected to buffered chemical polishing or to electropolishing; and van Gurp [ 41 ] observed higher i c values for cold rolled Nb foils compared to electrolytic Nb foils.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to bulk pinning, surface irregularities have also been shown to be effective at enhancing the critical current in conventional low-T c superconductors [36,37]. Among the procedures used to create surface defects in these materials are sandblasting [37], mechanical abrasion [38], buffered chemical or electrolytic polishing [39], and low temperature bakeout [40]. More recent work in metallic niobium sheets has shown that laser-induced periodic structuration can make the irreversibility field H irr increase [41], or decrease when using a femtosecond-pulsed laser [42].…”
Section: Introductionmentioning
confidence: 99%